(untitled) (Journal of Engineering, 2010)
This paper presents the building of expert system to enable the inexperience plants operators to application of better of wastewater treatment plant. This methodology consists of three steps: (i) creation of a decision trees (algorithms) for the diagnosis operational problems; (ii) implementation into a real-based system; and (iii) verification. This system called expert system for Rustimiyah south wastewater treatment plant operation (ES-RS-WWTPO). The knowledge acquisitions to build this system ware extracted from literature. Moreover local experience ware also incorporated using the results of a well designed questionnaire. The results obtained in the application three operational states showed that the system was able to diagnosis (correctly) state of plant with reasonable accuracy. The programmer language for built this system id Visual Basic 6.0.